Superficial Lymphadenomegaly (SL): clinico-pathological correlation in 154 patients of the National Hospital Cayetano Heredia, Lima, Perú - Osores Plenge, Fernando (2024)
Introduction: enlargement of superficial lymph nodes is a frequent clinical finding which may be among the first evidences of a significant illness or of a specific clinical syndrome.Objective: exploring clinico-pathological relationships in patients consulting for the first time with a clinically detectable lymphadenopathy and no defined diagnosis.Materials and Methods: cross sectional prospective study including patients with clinically detectable lymphadenopathy (nodes over 1 cm in diameter) and often also suspicion of tuberculosis. Lymph node biopsies, fine needle aspirations, and other contributing diagnostic tests were performed. A histopathological classification was structured to arrange the information on the patients and to correlate laboratory findings with clinical ones.Results: patients recruited were 154; 55 (45.5%) out of 70 patients who had a tentative diagnosis of tuberculosis or other mycobacterial disease had it confirmed by histopathology and culture; 31 (20.1 %) patients had non-specific lymphadenopathy, with no definitive etiological findings. In the remainder of patients there were several different definitive diagnoses: cat-scratch disease, mycoses, Kaposis sarcoma, lymphomas, metastatic neoplasias and acute retroviral syndrome caused by HIV infection.Conclusion: lymphadenopathy is a valuable sign for clinical diagnosis of many sometimes unsuspected diseases. Physicians should know how to decide when to order a lymph node biopsy and how to interpret the resulting histopathological findings, to improve diagnostic certainty.